Biases and Strategic Behaviour in Performance Evaluation: The Case of the FIFA's best soccer player award. (21st June 2017) - Coupe, Tom; Gergaud, Olivier; Noury, Abdul
Abstract: In this paper, we study biases in performance evaluation by analysing votes for the FIFA Ballon d'Or award for best soccer player, the most prestigious award in the sport. Our findings suggest that 'similarity' biases are substantial, with jury members disproportionately voting for candidates from their own country, own national team, own continent and own league team. Further, we show that the impact of such biases on the total number of votes a candidate receives is fairly limited and hence is likely to affect the outcome of this competition only on rare occasions where the difference in quality between the leading candidates is small. Finally, analysing the incidence of 'strategic voting', we find jury members who vote for one leading candidate are more, rather than less, likely to also give points to his main competitor, as compared with neutral jury members. We discuss the implications of our findings for the design of awards, elections and performance evaluation systems in general and for the FIFA Ballon d'Or award in particular.